The impact of multiple driving factors on forest ecosystem services in karst desertification control - Xiong, Kangning; Kong, Lingwei; Yu, Yanghua; Zhang, Shihao; Deng, Xuehua (Frontiers in Forests and Global Change, 2023)
In the fragile karst desertification ecosystem, forests are the providers of eco-multifunctionality. And the ecosystem service (ES) supply capacity of forests is directly or indirectly affected by various driving factors. The aim of this study is to explore the driving role of forest spatial structure, species diversity, and functional diversity on ecosystem services. In this study, four forest types, namely, broad-leaved monoculture forest (planted economic forest) (F1), broad-leaved mixed forest (F2), coniferous and broad-leaved mixed forest (F3), and coniferous mixed forest (F4), were investigated in karst plateau mountain (KPM), karst plateau canyon (KPC), and karst mountain canyon (KMC) landforms. Variance analysis, correlation analysis and redundancy analysis were used to compare the differences of spatial structure, species diversity, functional diversity, and ES of different forest types and to clarify the driving role of spatial structure, species diversity, and functional diversity on ES. The results showed that the wood supply service of F3 was at least 4.27% higher than that of other forest types; carbon sequestration and oxygen release are at least 4.57 and 3.89% higher; the water holding capacity of litter and soil is higher by 6.24 and 2.26%, respectively; the soil OC, TN, TP, and TK were higher than 6.01, 1.22, 25.55, and 13.34%, respectively. The coniferous mixed forest and broadleaved mixed forest with a more complete spatial structure has a higher level of diversity, which can generate more wood and provide more soil nutrient sources, as well as stronger regulation capacity. Spatial structure affects plant productivity through interspecific relationships; soil fertility is restricted by the level of diversity; gas and water regulation are influenced by both spatial structure and diversity levels. There is a progressive driving relationship among spatial structure, diversity, and ES. In forest management, it is helpful to improve the forest ecosystem’s functioning by adjusting the forest structure using close-to-natural management measures.